Physical and Physiological Profiles of Brazilian Jiu-Jitsu Athletes: a Systematic Review - Andreato L.V.* (2017)
© 2017, The Author(s).Background: Brazilian jiu-jitsu is a grappling combat sport that has intermittency as its core element; in other words, actions of high, moderate and low intensity are interspersed during matches, requiring a high level of conditioning to support optimal levels of performance for the total match time. The athletes perform from four to six matches during a day of competition, and this number may increase if the open-class competition, which is held parallel to the competition by weight class, is considered. This systematic review examined the physical and physiological profiles of Brazilian jiu-jitsu athletes. Methods: Only scientific researches dealing with the major fitness components of Brazilian jiu-jitsu athletes (i.e. body composition and somatotype, aerobic and anaerobic profiles, muscular strength and power) and using accepted methods that provided relevant practical applications for a Brazilian jiu-jitsu athlete’s fitness training and/or performance were included in the current review. A computer literature search was carried out of the PubMed, ISI Web of Knowledge, SportDiscus and Scopus databases (up to January 2016). Results: The database research generated 205 articles. After the application of inclusion and exclusion criteria, 58 studies were included for the present systematic review. A total of 1496 subjects were involved in all the selected investigations. Conclusions: Body fat is generally low for these athletes and the mesomorphic component is predominant. The different studies showed VO2max values between 42 and 52 mL/kg/min, and it seems that aerobic fitness does not discriminate among Brazilian jiu-jitsu athletes of different competitive levels. There is a lack of scientific studies that have investigated anaerobic responses both in lower and upper limbs. Maximal dynamic, isometric and endurance strength can be associated with sporting success in Brazilian jiu-jitsu athletes. Although decisive actions during Brazilian jiu-jitsu matches are mainly dependent on muscular power, more specific studies are necessary to describe it. Studies involving the female sex should be conducted. In addition, further research is needed to analyse whether there are differences between sex, belt ranks and competitive level, and among the different weight categories for different variables.